Penilaian Autentik Pembelajaran Akidah Akhlak - Rizza Fahlevy; Anisah Triyuliasari; Ichwanudin (Journal Islamic Education, 2024)
Authentic assessment in the teaching of Aqidah and Akhlak plays a crucial role in holistically measuring students' understanding of the values of faith and noble morals. This article aims to explain the concept of authentic assessment based on its definition, assessment standards, principles of approach, and relevant techniques and instruments. The discussion begins by defining authentic assessment standards, which refer to the accuracy, relevance, and meaningfulness of assessment data according to the curriculum. Assessment principles, such as the integration of cognitive, affective, and psychomotor aspects, are also examined in depth to ensure a holistic approach. The scope of authentic assessment includes evaluation of learning processes, outcomes, and the impact they have on student character development. Techniques used include observation, interviews, written tests, projects, portfolios, and self- and peer-assessments. To ensure the validity of the assessment, the instruments used must have validity, reliability, and sensitivity to individual differences. Assessment mechanisms and procedures are discussed systematically, from planning and implementation to reporting assessment results. Planning involves developing learning achievement indicators and selecting appropriate methods. Assessment is carried out through direct observation and objective recording of student performance. Assessment results are then reported in an informative format, reflecting comprehensive learning outcomes, both quantitatively and qualitatively. This article concludes that authentic assessment in Aqidah Akhlak learning aims not only to measure learning outcomes but also to shape character and enhance the internalization of moral values in students' daily lives. Therefore, a deep understanding and application of appropriate procedures are required so that assessment can provide optimal benefits for students' comprehensive development.